The Effect Of Price, Promotion And Ease Of Access On The Decision To Use The Maxim Application Service In The City Of Bengkulu - Anggara, Yogi; Abi, Yudi Irawan; Effendi, Yanto (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine the effect of price, promotion, and ease of access on the decision to use Maxim services in Bengkulu City, both partially and simultaneously. Data collection was conducted using a questionnaire. The sample consisted of 114 Maxim app service users in Bengkulu City. The analysis methods used were validity testing, reliability testing, multiple linear regression, coefficient of determination, F-test, and t-test.Based on the results of the research and discussion, it was found that price did not have a significant effect on the decision to use Maxim services in Bengkulu City because the significance value was 0.386 > 0.05. Promotions had a significant effect on the decision to use Maxim services in Bengkulu City because the significance value was 0.000 < 0.05. Ease of access has a significant effect on the decision to use Maxim application services in Bengkulu City because the significance value is 0.000 < 0.05. Meanwhile, simultaneously, price, promotion and ease of access have a significant effect on the decision to use Maxim application services in Bengkulu City because the significance value is 0.000 < 0.05.